Integrated business model for bio-fortified rice and diversified crops in Bangladesh - Ahmed, Sharif; Miajy, Abu Abdullah; Alanuzzaman Kurishi, A.S.M.; Krupnik, Timothy J.; Veettil, Prakashan Chellatan (TAFSSA, 2024)
This brief shows TAFSSA’s (Transforming Agri-food System in South Asia) market linkage activities for biofortified rice and diversified crops in different districts which were selected as the learning landscape location in Bangladesh. It also highlighted how TAFSSA is working to expand and develop integrated market systems for biofortified rice and diversified crops. It may help researchers and policymakers develop future activities on diversified crop expansion in Bangladesh.